The Potential Role of Extracellular Vesicles in COVID-19 Treatment: Opportunity and Challenge - Yan, Yan-yan; Zhou, Wen-min; Wang, Yu-qing; Guo, Qiao-ru; Zhao, Fu-xi; Zhu, Zhuang-yan; Xing, Yan-xia; Zhang, Hai-yan; Aljofan, Mohamad; Jarrahi, Alireza Mosavi; Makabel, Bolat; Zhang, Jian-ye (Frontiers in Molecular Biosciences, 2021)
SARS-CoV-2 infection has become an urgent public health concern worldwide, severely affecting our society and economy due to the long incubation time and high prevalence. People spare no effort on the rapid development of vaccine and treatment all over the world. Amongst the numerous ways of tackling this pandemic, some approaches using extracellular vesicles (EVs) are emerging. In this review, we summarize current prevalence and pathogenesis of COVID-19, involving the combination of SARS-CoV-2 and virus receptor ACE2, endothelial dysfunction and micro thrombosis, together with cytokine storm. We also discuss the ongoing EVs-based strategies for the treatment of COVID-19, including mesenchymal stem cell (MSC)-EVs, drug-EVs, vaccine-EVs, platelet-EVs, and others. This manuscript provides the foundation for the development of targeted drugs and vaccines for SARS-CoV-2 infections.